2015
DOI: 10.1140/epjc/s10052-015-3539-x
|View full text |Cite
|
Sign up to set email alerts
|

Shadows of CPR black holes and tests of the Kerr metric

Abstract: We study the shadow of the Cardoso-Pani-Rico black hole for different values of the black hole spin a * , the deformation parameters t 3 and r 3 , and the viewing angle i. We find that the main impact of the deformation parameter t 3 is the change of the size of the shadow, while the deformation parameter r 3 affects the shape of its boundary. In general, it is impossible to test the Kerr metric, because the shadow of a Kerr black hole can be reproduced quite well by a black hole with non-vanishing t 3 or r 3 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 111 publications
0
50
0
Order By: Relevance
“…These figures show both the shape of the black hole shadow (on the left in each panel) and the function R(φ), which was introduced in Ref. [38] to characterize the shape of the shadow (see Ref. [39] for a more sophisticated description).…”
Section: Black Hole Shadowmentioning
confidence: 99%
“…These figures show both the shape of the black hole shadow (on the left in each panel) and the function R(φ), which was introduced in Ref. [38] to characterize the shape of the shadow (see Ref. [39] for a more sophisticated description).…”
Section: Black Hole Shadowmentioning
confidence: 99%
“…This has been the subject of a recent study by Ref. 73, who showed that the near-field image by itself might not be able to detect a deviation from Kerr (as an illustration, see their Figure 5a). However, once the spin measurement from the pulsar done in the Kerr-like far field is combined with the constraints from modeling the shadow, one can recover the deformation (in their case, parameter t 3 ), and test for a violation of the Kerr hypothesis.…”
Section: Combining the Constraints From Different Techniquesmentioning
confidence: 97%
“…Ref. 73). The combination of different methods can in fact break this degeneracy and therefore lead to independent estimates of the BH parameters and to a clean test of the Kerr metric.…”
Section: Combining the Constraints From Different Techniquesmentioning
confidence: 99%
“…This has been the subject of a recent study by Ref. 175, who showed that the near-field image by itself might not be able to detect a deviation from Kerr (as an illustration, see their Fig. 5(a)).…”
Section: Combining the Constraints From Different Techniquesmentioning
confidence: 97%
“…Ref. 175). The combination of different methods can in fact break this degeneracy and therefore lead to independent estimates of the BH parameters and to a clean test of the Kerr metric.…”
Section: Combining the Constraints From Different Techniquesmentioning
confidence: 99%